A reliable open-source package for performance evaluation of floating renewable energy systems in coastal and offshore regions. (15th October 2018) - Liu, Yingyi; Yoshida, Shigeo; Hu, Changhong; Sueyoshi, Makoto; Sun, Liang; Gao, Junliang; Cong, Peiwen; He, Guanghua
Graphical abstract: Highlights: A region-decomposition strategy is developed to compute the free-surface Green's function. The numerical code is written in a multi-level hierarchical structure using the modern Fortran. General-shaped geometries and two complex-shaped wind turbine floaters have been studied. Results show that the FinGreen3D can predict wave loads as accurate as analytical methods. The numerical software package is publicly released as an open source tool on GitHub. Abstract: The booming developments of coastal/offshore renewable energies in recent years call for a powerful numerical code, ideally open-source packaged, to accelerate the researches in the spotlight. This paper presents such an efficient software package for evaluating the performance of floating renewable energy systems in the coastal and offshore regions. It aims to contribute an open-source effort in numerical simulations for ocean energy converters. Though computation of the free-surface effect in moderate depth region is extremely troublesome due to the singularities, the software package proposed in the present paper gives a satisfactory solution to keep the balance of accuracy and efficiency. In the present paper, the interface and structure of the package are introduced in detail so as to be well understood by the reader. Benchmark tests for various types of converters have confirmed the accuracy and efficiency of the package which can be incorporated easily with a frequency domain solver for efficient analysis. By contributing as one of the pioneer works in the open-source effort of evaluating the moderate-depth free-surface Green's function, with its advantages of a reliable accuracy and a relatively low cost, the authors are hoping that the publication of the present software package will promote the continuous researches in developing robust and reliable coastal and offshore renewable energy systems.